2006
DOI: 10.1177/112972980600700209
|View full text |Cite
|
Sign up to set email alerts
|

The brachio-brachial arteriovenous fistula: a new method in patients without a superficial venous system in the upper limb

Abstract: The brachio-brachial fistula can represent a viable choice in patients with an inadequate superficial venous system in the upper limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…8 Previous reports have described successful AVF-Ts using not only the basilic vein for access but also the brachial vein, forearm, and thigh veins. [20][21][22][23][24][25][26][27] Staged AVF-Ts have previously been described. 5,28 Hill et al 29 found AVF-Ts using basilic veins Ͼ4 mm in diameter had a higher success rate than AVF-Ts using smaller veins.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous reports have described successful AVF-Ts using not only the basilic vein for access but also the brachial vein, forearm, and thigh veins. [20][21][22][23][24][25][26][27] Staged AVF-Ts have previously been described. 5,28 Hill et al 29 found AVF-Ts using basilic veins Ͼ4 mm in diameter had a higher success rate than AVF-Ts using smaller veins.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles were identified and fulfilled the inclusion criteria. 2,[4][5][6][7][8][9][10][11][12][13][14] According to our analysis, results presented a great fluctuation in heterogeneity and patency rates. Overall, 380 BVT-AVF were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Literature regarding CVT is sparse (17). Other techniques using the brachial vein (26) or translocated femoral vein (27) have been reported, with acceptable results. However, due to extensive dissection and morbidity, these procedures have not become popular.…”
Section: Discussionmentioning
confidence: 99%